Penentuan Penerimaan Bantuan Masyarakat Menggunakan Metode Weight Product (WP) - Baina Sahara; Budi Serasi Ginting; Siswan Syahputra (Journal of Computer Science and Informatics Engineering, 2022)
Nangka Village, North Binjai District, Binjai City is one of the villages that proposes and distributes assistance to the community. The current problem in the scheme of assistance to the community is the inaccuracy of recipient data. This can raise concerns that if there is no improvement it will lead to social conflict in the community. Efforts that can be made to overcome these problems in recording and determining the people who are entitled to receive assistance for the community are by using a Decision Support System (SPK) with the Weighted Product (WP) Method to implement the determination of acceptance of community assistance. The criteria used are income, number of dependent children, floor area, type of house wall, home ownership status, source of lighting, cooking fuel, and education of the head of the household